Close or Distant? – Contemporary Reception, Construction and Deconstruction of the Idea of Freak Show - Skręt, Katarzyna (Not just the Clown and the Tiger. Sketches about Circus Arts, 2019)
The author draws attention to the reception of a peculiar body exposed to the show: a living body (which is involved in the shows) and a dead body (which is made available to viewers after death). Such optics determines to take up the subject of transgression and related dualizum of the sacred/profane (within the meaning of Georges Bataille). The author finds an interesting, in her opinion, reception of the idea of freak show in the manifestations of contemporary culture: the dramatic text (Miss Julia Pastrana by Joanna Gerigk), the cinema (Freaks by Tom Browning, 1932 and the series American Horror Story: Freak Show, 2014) and plastic surgery (body modifications which make people look like ‘freaks’). The analysis of these issues will draw attention to the differences and similarities between ‘ordinary’ people and human curiosities.